Business Transformation: Exploring Dynamic Capabilities, Technological Innovation, and Competitive Advantage through the Lens of Resource-Based View in Construction Services Companies - Wibisono, Hari; Supoyo, Maryono (ADMAN: Journal of Contemporary Administration and Management, 2023)
Construction services companies, as an integral part of the construction sector, face significant challenges in coping with rapidly changing business environments. In the face of this uncertainty, business transformation becomes a necessity to ensure the sustainability and success of the company. This research aims to explore the relationship between business transformation, dynamic capabilities, technological innovation, and competitive advantage in construction services companies. The research utilized an extensive examination of existing literature employing qualitative analysis to acquire a comprehensive insight into the subject, covering the period from 1991 to 2023. The study results indicate that in the era of globalization and business dynamics, business transformation is crucial for construction services companies. The Resource-Based View (RBV) approach emphasizes the importance of internal resources and capabilities such as technical skills, managerial skills, innovation, and rapid adaptation to changes. The implementation of technologies such as BIM, IoT, and AI is key to enhancing efficiency and expanding interactions with customers. Successful transformation requires a focus on the development of unique resources and capabilities, rapid adaptation to market and technological changes, and customer engagement by understanding their needs and providing excellent services.